Proteinopatije - bolezni odlaganja napačno zvitih beljakovin - Popović, Mara (Medicinski razgledi, 2008)
Proteinopathies are protein deposition diseases caused by misfolded proteins. Molecules of misfolded proteins are prone to aggregate and damage the tissue, and eventually they may kill the patient if a vital organ is affected. There are many causes of protein misfolding, including gene mutations, failure in gene transcription or post-translational protein folding despite normal primary structure, protein overproduction and aberrant proteolysis. Risk factors for non-genetic proteinopathies are ageing, certain chronic diseases, certain tumors and dialysis. Misfolded protein could be deposited in the extracellular matrix or inside the cells, forming different inclusions. So far, more than 25 proteins have been identified to be prone to misfold and cause the disease. Based on the structural and tinctorial properties of misfolded protein aggregates, proteinopathies are divided to amyloidoses and non-amyloid proteinopathies. Proteinopathies can be systemic or localized, when several or only one organ is involved, respectively. The most frequent systemic proteinopathy is systemic amyloidosis which involves the deposition of immunoglobulin light chains, and the most frequent localised proteinopathy is Alzheimer's disease. Proteinopathies can be named by the misfolded proteins: monoclonal immunoglobulin deposition disease, tauopathies, synucleinopathies, prionopathies etc. Proteinopathies are progressive diseases, but most of them are so far incurable.
Keywords: Amyloidosis; Paraproteinemije; Parkinsonova bolezen; Paraproteinemias; Alzheimer'S Disease; Amiotrofična, lateralna skleroza; Amiloidoza; Parkinson Disease; Živec, degeneracija; Amyotrophic Lateral Sclerosis; Nerve Degeneration; živčevje; proteinopatije; Alzheimerjeva bolezen; degenerativne bolezni